Investigations on Ultrasonic Copper Wire Wedge Bonding for Power Electronics - Kästle, Christopher; Syed Khaja, Aarief Hussain; Reinhardt, Andreas; Franke, Jörg (Proceedings of the 36th International Spring Seminar on Electronics Technology (ISSE), 2013)
Driven by applications in the field of renewable energy, power distribution, consumer electronics and the automotive industry, the demand for reliable and economic power electronics packaging solutions is growing rapidly. The present study aims to display a new technology for chip top-side interconnects by using heavy wire copper wedge/wedge bonding. Therefore a response surface design of experiment study was set up to evaluate the influence of the main parameters time, ultrasonic power and bond force on the bond process quality. With this information an optimized set of machine parameters was derived, with respect to maximized pull and shear forces. Furthermore, investigations on the correlation between the bond parameters and the destructive test failure modes were conducted. All tests were accompanied by a monitoring of the tool wear-out. This allows to assess the process stability as well as the process reliability. The aim is to identify the most significant parameters and to find an optimized parameter set in order to improve future die interconnection technologies for power electronics manufacturing.
Keywords: copper wire bonding; power electronics; reliability; wedge bonding